KARAKTERISTIK KIMIA DAN FISIK SISIK IKAN GURAMI (Osphronemus gouramy) - NURJANAH NURJANAH; RUDDY SUWANDI; VANADIA YOGASWARI (Akuatik: Jurnal Sumberdaya Perairan, 2010)
Scales of fish represent side product which not yet been exploited optimally. Fish scales in industrial scale (side product of fish fillet industry) can be used as collagen source, while in domestic scale generally only thrown. This research aim to know fish scales potency by determining rendemen, chemical composition and physical, and possibility of existence active component in fish scales. If the target point have been known, hence which wish known hereinafter is influence of fish weight toward content of fish scales. Result of research on fish scales of carp with 260-3.315 gram in weight is rendemen mean of carp scales from 3,0-5,7 %. Carp scales is over three big component which is protein 29,8-40,9%, water 30,0-36,8%, and dusty 18,7-26,3% ( content of calcium 5,0-8,6%). Other component are fat 0,1-1,0 % and carbohydrate by differences 2,0-5,7 % ( content of chitin 0,4-3,7 %). Carp scales is alkalis, pH 8,0-8,7. Carp scales thickness is 0,02-0,07 mm and diameter range is 0,9-2,1 cm. Carp scales contain alkaloid, carbohydrate, compound of peptide, and amino acid. Carp weight have an effect on chitin rate. Ever greater of carp weight, progressively have lower chitin rate at its scales